Temple of Aaron confirmation class, St. Paul (Jewish Historical Society of the Upper Midwest, 4330 S. Cedar Lake Road, Minneapolis, MN 55416. http://www.jhsum.org/asp_pages/index.asp)
255463db025f1f77f386e239e5534668
United States
Minnesota
Ramsey
St. Paul
255463db025f1f77f386e239e5534668
Keywords: Religious events--synagogue-sponsored--Conformation; Youth groups; Religious education; Religion